Kecemasan antara siswa smp dan santri pondok pesantren - M. Afif Aminullah (Jurnal Ilmiah Psikologi Terapan, 2014)
Many school age teenagers experience anxiety, especially when participating in the learning process at school, including junior high school students and class I Islamic boarding school students who have just entered a new school. This research aims to determine the differences in anxiety between junior high school students and class I Islamic boarding school students. The design used is a quantitative descriptive non-experimental design. Data was collected using the Taylor Manifest Anxiety Scale (TMAS) which consists of 50 items. The sample for this study was 84 people. Research analysis uses T-test. Based on the results of the analysis, it shows that there is a difference in anxiety between junior high school students and class I Islamic boarding school students with a very significant value (t=4.64, p=0.000). The anxiety of class I Islamic boarding school students is higher (39.3%) than class I junior high school students (20.2%).